Refractive index changes in photochromic SbPO4-WO3 glass by exposure to band-gap radiation - Ahlawat, Meenu; Vazquez, Gloria V.; Nalin, Marcelo [UNESP]; Messaddeq, Younes [UNESP]; Ribeiro, Sidney [UNESP]; Kashyap, Raman (Elsevier B.V., 2010)
We report photoinduced photo-darkening in SbPO4-WO3 glass by exposure to 532 nm light with a power density of 143 mW/cm(2). The time of exposure was varied between 0 and 256 min following which visible photo-darkening, peaking at 850 nm was observed. Spectrophotometer measurement of absorption was performed for both treated and untreated regions of the sample. Time exposure to below band-gap light results in a single exponent Gaussian absorption function over an exceptionally wide range of wavelengths (500 nm-1600 nm), with a 1/e width of 647.5 nm. Kramers-Kronig transform of the change in the absorption indicates a negative local change in the refractive index. The dispersed refractive index change at 1550 nm, Delta n, is calculated to be similar to -5 x 10(-8). The peak absorption increases with time of exposure and the photo-darkening remains irreversible at room temperature. Crown Copyright (C) 2010 Published by Elsevier B.V. All rights reserved.
Keywords: Photoinduced effects; Refractive index; Kramers-Kronig; Antimony